GOVERNMENT COALITION PARTIES' INTEREST CONFLICT AND THEIR ETHICS BASED ON SURAH AL-MUMTAHANAH - Iman, Sunardi Bashri (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
A multi-party system of governance, which is based on idiosyncratically and culturally diverse identities, is so prone to disintegration that it will erode public trust. Government confidence and authority declined as a result of problems that emerged as government coalitions were formed. The most notable of these included the rejection of influence, the politicization of the law, the arrogance of officials, the repudiation of offices, and the accumulation of wealth in unwarranted ways. The author's motivation to solve the formula problem, "What is the ethics of coalition multi-party government from the perspective of the Quran's interpretation of Surah Al-Mumtahanah verses eight and nine?" stems from the aforementioned issue. Descriptive and qualitative analysis research on the ethical normative analysis conducted in the Republic of Indonesia's cabinet between 2019 and 2024 is associated with the principles of Quranic ethics, which call for cooperation. The novel observation made by the author is that the coalition is a close-knit political organization that does not marginalize friends and instead stands tall and sits low, unlike a two-legged, power-sharing political party. Coalitions also foster cooperation, which advances mankind, fosters justice, and unites people.